Malotas (b), a new eucrite from an old fall. (17th November 2022) - Saavedra, Marcela E.; Roszjar, Julia; Riebe, My E. I.; Varela, María E.; Yang, Shuying; Humayun, Munir; Tanaka, Ryoji; Busemann, H.
Abstract: On the night of June 22, 1931 at 4 h 30 min, a fireball was seen in the vicinity of Malotas, Argentina. During the atmospheric trajectory (southwest to northeast), it experienced several fragmentation events. After the fall, a piece was given to Professor Juan A. Olsacher (National University of Córdoba City, Argentina), who collected some further pieces. One of those samples was officially classified as an H5 ordinary chondrite termed Malotas. The present work focuses on the study of another two pieces rediscovered recently in the Museo de Mineralogía y Geología Dr. Alfred Stelzner in Cordoba City, Argentina. The first piece turned out to be an achondritic meteorite termed Malotas (b). Petrographic features, chemical composition, and oxygen isotopes point to a monomict basaltic eucrite belonging to the Stannern‐trend chemical subgroup of eucrites. The occurrence of anorthitic plagioclase veins in clinopyroxene, veinlet apatite, irregular‐shaped pockets of silica and troilite and porous silica signal metasomatism and thermal annealing before a late thermal event took place after brecciation. The latter was possibly recorded in the nominal U/Th‐ 4 He ages of 1.2–3.4 Ga detected in this work, whereas nominal K‐Ar gas retention ages are within the range 3.5–4.2 Ga and may have escaped late thermal modifications. The second piece is classified as an L5 chondrite. The different cosmic ray exposure ages of 3, 50, and 27 Ma determined for the H5 and L5 chondrites and the eucrite samples, respectively, might signal a common fall as a result of the breakup of a polymict meteoroid.